Mapping Investment Decision Studies: A Bibliometric Review - Avnner Chardles Wellfren; Nelson Lajuni (Human Resource Management Academic Research Society (HRMARS), 2022)
The significance of investment decisions has increased the field's value among, particularly for investors and researchers. In this study, our review attempts to map trends and development of investment decision studies in the past, present and potential new knowledge or significant gaps in the literature for future references by utilizing bibliometric analysis. This study investigated a total of 3,894 papers retrieved from the Scopus database between 1990 and August 2021. The mapping revealed an upward trend of publications and is expected to continue in the next few years. Simultaneously, analysis based on Harzing's Publish and Perish and VOSviewer has demonstrated the significant increase of investment decisions studies as a result of emerging themes, mostly driven by technology advancement and social movement. Financial reporting and environmental, social, and governance (ESG) issues have been increasingly popular among researchers in recent years. Our mapping exposes the popularity of this topic among past, current and future researchers. As a result, this study's main value is the expansion of knowledge in investment decisions and as foundation for future academic reference. Stakeholders such as policymakers, industry players including scholars should explore potential areas in investment decision studies that will benefit the public as a whole.